Penggunaan 3D Landmark Untuk Pengenalan Masjid Di Kota Bekasi Menggunakan Metode Prototype - Ruseno, Ndaru; Satria, Satria (KILAT, 2021)
The mosque is the center of Muslim activities. The development of the mosque at this time so fast it can be seen from the City to remote villages. Bekasi City has 12 districts and in each district there are already many mosques that are easy to find. Each mosque must have a different architecture. The difference of each mosque building architecture is what makes Muslims want to visit the mosques to find out the beauty contained in the mosque's architecture. many of them first do a search on the search engine to find the mosque you want to visit Results Unfortunately on the search results there are still many who are drawn in 2D in the form of photographs of the mosque. 2D depiction is considered less effective because it can only see from one angle. Visualization is engineering in making drawings, diagrams, or animations to display information. Visualization usually depicts objects in 3D. With visualization, mosque objects can be shown as a whole. The research conducted is the prototyping method, where this method is used starting in the initial stages of design until the application is ready for use. Through the output of the mosque mosque visualization application in the District of Bekasi City, the author wants to show the overall shape of the mosque, mosque data, and the location of the mosque to make it easier for users before choosing a mosque to visit through a mobile-based application. This application includes mosques from 12 Subdistricts in the City of Bekasi, where in one district is represented by one mosque. The making of this application uses the PHP programming language